Development of Information Management Information System for Learning Implementation Plan (RPP) for Senior High Schools (SMA) - Tjandra Tjahyarini (Jurnal Teknik Informatika C.I.T Medicom, 2018)
Preparation of Learning Implementation Plan (RPP) in senior high schools is generally done using Microsoft Word and archived in a way in print (hardcopy) .With berjalanya hardcopy filing period will take place and the process of accessing the RPP was less effective. RPP data access is required untukKegiatan Learning and Teaching (KBM) and for the renewal of the RPP made the beginning of each new school year. This can be overcome with the help of systems and information technology. A web-based information systems can be used to process data RPP, storing / archiving the data centrally so that effective and efisiien RPP accessing and archiving.